2007
DOI: 10.1007/s10994-007-0717-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dyadic decision trees

Abstract: We introduce a new algorithm building an optimal dyadic decision tree (ODT). The method combines guaranteed performance in the learning theoretical sense and optimal search from the algorithmic point of view. Furthermore it inherits the explanatory power of tree approaches, while improving performance over classical approaches such as CART/C4.5, as shown on experiments on artificial and benchmark data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 17 publications
1
51
0
1
Order By: Relevance
“…4 Algorithms for λ Blanchard et al (2007) suggest that the regularization parameter take the form λ = κ/n, and they show good empirical results for 1 ≤ κ ≤ 4. They also suggest a rule of thumb that chooses κ = 2 for a 2-class classification problem (Blanchard et al 2007).…”
Section: A Memoized Recursive (Mr) Algorithm For Minimizing R λmentioning
confidence: 99%
See 4 more Smart Citations
“…4 Algorithms for λ Blanchard et al (2007) suggest that the regularization parameter take the form λ = κ/n, and they show good empirical results for 1 ≤ κ ≤ 4. They also suggest a rule of thumb that chooses κ = 2 for a 2-class classification problem (Blanchard et al 2007).…”
Section: A Memoized Recursive (Mr) Algorithm For Minimizing R λmentioning
confidence: 99%
“…trees whose splits are determined by cycling through the coordinates and splitting at the interval mid-points) is guaranteed to be robust to distribution (Scott and Nowak 2003, 2004, 2006. Recently it has been shown that allowing the dyadic splits to be performed in arbitrary order, and then designing the tree to minimize a regularized risk, also yields robust performance guarantees (Scott and Nowak 2006;Blanchard et al 2007) and tends to give better results in practice (Blanchard et al 2007). The current best algorithm for designing these trees is the dynamic programming algorithm of Blanchard et al (2007) which was inspired by the "dyadic CART" algorithm of Donoho (1997).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations